Analysis of Writer Styles in Punjabi - Pandian, A.; Wahi, Stephen; Tokas, Yash; Manikandan, k.; V.Ramalingams, V. (International Journal of Engineering and Technology, 2018)
Author Identification alludes to the issue of distinguishing the creator of a mysterious content. From the machine learning perspective, this is a solitary mark content arrangement assignment. This errand is done on the supposition that the creator of an obscure content can be separated by looking at a couple of lexical highlights extricated from that obscure content with those of writings having known writers. In this paper, Authorship Identification process is connected on Punjabi verse dataset comprising of Punjabi ballads composed by 5 unique writers. Different highlights extensively ordered as measurable (word-check, roast tally, and so forth.), linguistic (i.e. lexical) and semantically (dialect subordinate) are first chosen utilizing the J48 Decision Tree Algorithm. They chose highlights are thusly, utilized as a contribution to the J48 classifier and the approval of the proposed framework is assessed based on Precision, Recall, F-score and Accuracy.Â Â